DAMPAK PENGGUNAAN GADGET TERHADAP INTERAKSI SOSIAL PESERTA DIDIK - Ana Muttabiah; Ela Suryani; Anni Malihatul Hawa (Universitas Ngudi Waluyo, 2021)
AbstractThe purpose of this study was to determine the effect of gadgets on the social interaction of students according to the results of a literature review. This research is in the form of a literature review according to studies which are the result of relevant research related to the topic of gadget use on students' social interactions. The results of the study show that the use of gadgets on students' social interactions has positive and negative consequences. The positive impact is that students can interact with distant friends wherever they are and at any time, while the negative impact is that children often play using gadgets instead of playing and interacting with people who are nearby, becoming anti-social, introverted and having difficulty concentrating on the real world. so that children become individualists.Keywords: gadget impact, leaners, sosial interaction